A COMPARATIVE STUDY OF PRE AND POST-OPERATIVE REFRACTIVE ERRORS IN CATARACT SURGERY - PHACO & SICS. - Dr. Santosh Kumar Singh; Dr. MD. Tabrez Alam (Student's Journal of Health Research, 2023)
Background:  The method of phacoemulsification for cataract surgery is preferred by surgeons, but it is not an affordable method. On the other hand, small-incision cataract surgery performed manually is economically affordable. This is a comparative study conducted prospectively to analyze the visual ability of the patients who had cataract extraction surgery by either of the methods. Methods:  50 patients had cataract extraction by phacoemulsification and another 50 patients who underwent manual incision cataract surgery were included in the prospective comparative study. The refractive errors and the visual acuity of the subjects were evaluated in the follow-ups conducted after a day, three days, a week, three weeks, for weeks, six weeks, and 12 weeks after the surgery. The results obtained were statistically compared. Results:  The observations of the refractive errors after the surgery were comparable in both methods. The difference in the refractive errors was significant with phacoemulsification and manual small-incision cataract surgery. However, the visual acuity was better than the preoperative baseline visual acuity. Conclusion:  Phacoemulsification is a superior method for cataract surgery when compared to the manual incision method in terms of the occurrence of refractive errors after the surgery. Recommendation: The history of any ocular surgery or contact lens use must be documented. Accurate preoperative measurements should be verified and repeated if they do not make sense.